Look east to act east: transforming India-ASEAN relations in Modi Era - Singh, Sudhir (ed.) (New Delhi Pentagon Press LLP, 2020)
Act East Policy launched in 2014 has been one of the signature foreign policy approaches of Modi-1 government and is a proactive foreign policy initiative. The movement from Look East to Act East was necessitated by the changing contours of security architecture in the larger context of the Indo-Pacific region. Act East Policy has further expanded the geography within its imprint; Myanmar to Australia comes under its domain. ASEAN and East Asian countries expect India to play a counter-balancing role within the region. Under Modi government, India has taken a principled stand on disputes like South and East China Seas stating that all disputing parties must adhere to international laws. This policy provides a broad canvass for issues ranging from economy, culture to strategy. The re-election of Modi with a larger majority in May 2019 is bound to consolidate the Act East Policy. India has developed convergences with many important countries of the region under the ambit of this policy and it is bound to pay more dividends in the foreseeable future for India`s national interests.
Keywords: Southeast Asia; Politics and government